(untitled) (Research, Society and Development, 2021)
The current development and reliability of adhesive systems and composite resins offer good options for treating and managing the loss of tooth structures. Patients with minimal, moderate or severe wear can be treated minimally invasively with adhesive composite restorations. Thus, according to the knowledge from clinical practice and based on the scientific literature on the topic discussed; and considering the different possibilities of conducting the case presented, it was proposed to carry out the rehabilitation of the maxilla and mandible with the use of Aesthetic and Functional Rehabilitation with Pressed Composite Resins (AFRPCR) with heated conventional viscosity composite resin and flow composite resin. Procedure performed for the immediate restoration of the vertical dimension of occlusion (VDO), functional diagnosis, and aesthetic treatment with excellent prognosis. In addition, this clinical case presents and discusses the general aspects about its importance, indication, applicability and clinical management. AFRPCR is a simplified, safe, reversible, conservative, low-cost treatment compared to ceramic prostheses, which meets clinical needs quickly with high predictability, reproducibility, longevity and has wide application within different oral rehabilitation treatments, however, it is an "operator-sensitive" technique that requires a certain skill and training on the part of the dental surgeon, a correct and meticulous diagnostic wax-up and impression materials with high reproduction of details and dimensional stability.